Груповий соціальний потенціал: поняття, основні ознаки та складові - Коленда, Наталія Вікторівна; Kolenda, Nataliia Viktorivna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на основі емпіричного аналізу та узагальнення визначено ознаки групового соціального потенціалу та подано авторське трактування його сутності. Виокремлено складові групового соціального потенціалу та дано їх характеристику. Розглянуто види групового соціального потенціалу. The levels of social potential, including: nano-, micro-, macro- and metalevel and its carrier are certain in the article. In research attention is concentrated on the study of group social potential, that is formed on a nanolevel and it carriers are families, certain groups, associations, community. Based on generalization and systematization of works of scientists and results of previous researches of author, it was succeeded to distinguish the signs of group social potential and basis of it to give own vision of the essence of this concept as possibilities of group of people to act and achieve a joint purpose, that is formed in the process of socialization and establishment of stable social relations and focused on appropriation of resources and their further effective use with the purpose of obtaining a synergistic effect. The component structure of group social potential are offered and types considering the formed criteria are selected.
Group social potential: concept, main features and components
Keywords: соціальний потенціал; social potential; груповий соціальний потенціал; група; колектив; людський потенціал; репродуктивний потенціал; комунікативний потенціал; організаційний потенціал; group social potential; group; collective; human potential; reproductive potential; communicative potential; organizational potential